1998
DOI: 10.1002/(sici)1097-0142(19980825)84:4<202::aid-cncr4>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

The promise and risk of a new technology

Abstract: Preliminary experience at Lehigh Valley Hospital suggests that the promise of liquid‐based cervical cytology preparation not only improves sensitivity of the cytology test but also greatly enhances the overall quality of the cervicovaginal cytology service. Although the promise appears to be real, cautious optimism is indicated. In the future, more liquid‐based cervicovaginal tests coupled with outcome studies will help in the evaluation of whether liquid‐based systems truly allow better determination of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…All unsatisfactory LBC results were due to scant cellularity, perhaps reflecting high levels of cervical atrophy in our population of older women, aged 35-65. Some previous studies have also found that LBC has a higher unsatisfactory rate, 13,[18][19][20] although others have not. 12,14,16,17,21 A number of meta-analyses and systematic reviews have assessed the results of previous studies comparing LBC and conventional cytology with differing conclusions regarding test performance depending on the study inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…All unsatisfactory LBC results were due to scant cellularity, perhaps reflecting high levels of cervical atrophy in our population of older women, aged 35-65. Some previous studies have also found that LBC has a higher unsatisfactory rate, 13,[18][19][20] although others have not. 12,14,16,17,21 A number of meta-analyses and systematic reviews have assessed the results of previous studies comparing LBC and conventional cytology with differing conclusions regarding test performance depending on the study inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical and scientific allure of liquid based technology has been explored extensively. 5 Most western countries have switched over from CPS to LBC, even though sensitivity and specificity is almost similar in various comparison studies. The reason for this may be consistently increased rates of satisfactory results for epithelial abnormalities on LBC, clarity of microscopy, improved sample processing, and small area to be screened.…”
Section: Discussionmentioning
confidence: 97%